Hard palate hyperpigmentation - a rare side effect of antimalarials - Manger, Karin; von Streitberg, Ulrich; Seitz, Gerhard; Kleyer, Arnd; Manger, Bernhard (Arthritis and Rheumatology, 2017)
A 50-year old female Caucasian patient with marked xerostomia, xerophthalmia, relapsing parotid swelling, arthralgias, and fatigue had been treated with chloroquine diphosphate (250 mg/day) for four years, when a painless bluish-grey hyperpigmentation of her hard palate was noticed during one of her rheumatologic follow-up visits (A). To rule out malignancy or infection, a mucosal biopsy was performed and histology showed subepithelial granular pigment depositions among collagen fibres and within macrophages (B). Perl's Prussian blue staining confirmed that these deposits contained hemosiderin (C). This article is protected by copyright. All rights reserved.
EVALuna2:13448